ALS1 Deletion Increases the Proportion of Small Cells in a Candida albicans Culture Population: Hypothesizing a Novel Role for Als1 - Xiaomin Zhao (Frontiers in Cellular and Infection Microbiology, 2022)
Candida albicans Als1 is a large cell-surface glycoprotein most often discussed for its role in mediating ligand-binding and aggregative interactions. Relative to a wild-type control, deletion of ALS1 produced a strain that showed delayed germ-tube formation and delayed disease progression in a murine model of disseminated candidiasis. Populations of Δals1/Δals1 cultured cells had a higher proportion of smaller cells compared to wild-type or ALS1 reintegrant control cultures. The goal of this work was to investigate whether this difference in cell-size distributions was responsible for delayed germ-tube formation and delayed disease progression. Flow cytometry was used to select populations of wild-type and Δals1/Δals1 cells with varied cell-size distributions. Delayed germ-tube formation was demonstrated for small cells sorted from a wild-type (ALS1/ALS1) culture population. Large cells sorted from a Δals1/Δals1 culture formed germ tubes as quickly as the wild-type control demonstrating clearly that the Δals1/Δals1 germ-tube formation delays were attributable to cell size. In vivo, smaller-sized cells of the wild-type control showed fewer colony-forming units (cfu) per gram of kidney tissue and less-severe histopathology lesions compared to larger cells of the same strain. The Δals1/Δals1 strain showed reduced cfu/g of kidney tissue and less-severe lesions compared to the wild-type control. However, isolation and testing of the larger cells from the Δals1/Δals1 population increased cfu/g of tissue and showed increased lesion severity compared to the overall mutant cell population. In vivo hypha lengths from the large, sorted Δals1/Δals1 cells were comparable to those for the wild-type control strain. These results demonstrated that a large share of the Δals1/Δals1 in-vivo phenotype was attributable to cell size. Collectively, the data suggest a role for Als1 in C. albicans cell size homeostasis, a novel hypothesis for further exploration.